2021
DOI: 10.3389/fnhum.2021.717401
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Large-Scale Data Infrastructure in Developing Next-Generation Deep Brain Stimulation Therapies

Abstract: Advances in neuromodulation technologies hold the promise of treating a patient’s unique brain network pathology using personalized stimulation patterns. In service of these goals, neuromodulation clinical trials using sensing-enabled devices are routinely generating large multi-modal datasets. However, with the expansion of data acquisition also comes an increasing difficulty to store, manage, and analyze the associated datasets, which integrate complex neural and wearable time-series data with dynamic assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Patients with PD can experience residual motor fluctuations during optimized continuous deep brain stimulation (cDBS). Previous in-clinic and short at-home studies have suggested that adaptive DBS (aDBS), i.e., titrating stimulation amplitude in response to symptom-state-associated neural signals (i.e., biomarkers), could possibly alleviate residual symptoms (Little et al, 2013;Arlotti et al, 2018;Gilron et al, 2021a). It has been uncertain if these results can be replicated at-home for sustained periods.…”
Section: At-home Adaptive Deep Brain Stimulation For Parkinson's Dise...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with PD can experience residual motor fluctuations during optimized continuous deep brain stimulation (cDBS). Previous in-clinic and short at-home studies have suggested that adaptive DBS (aDBS), i.e., titrating stimulation amplitude in response to symptom-state-associated neural signals (i.e., biomarkers), could possibly alleviate residual symptoms (Little et al, 2013;Arlotti et al, 2018;Gilron et al, 2021a). It has been uncertain if these results can be replicated at-home for sustained periods.…”
Section: At-home Adaptive Deep Brain Stimulation For Parkinson's Dise...mentioning
confidence: 99%
“…These multimodal datasets can possibly be incorporated into routine clinical care to inform decisions about DBS – from patient selection, to DBS programming, to adaptive DBS ( Gilron et al, 2021a , b ; Fleming et al, 2022 ). However, collection and integration of these data require the development of new tools ( Chen et al, 2021a ). Using Rune Labs, we show an example of one patient who was continuously monitored for an entire year before and after implantation using a sensing enabled DBS, and we highlight ways in which this dataset paints a rich picture as compared to standard clinical scales.…”
Section: Alphadbs Is a New Implantable Closed-loop Clinical Neural In...mentioning
confidence: 99%
“…Three axes of accelerometry and gyroscope data were both collected at 50Hz. Recordings were automatically uploaded to a protected health information (PHI)-compliant third-party server (Rune Labs, Inc) [18], from which the data were later accessed for analysis.…”
Section: B Inertial Sensingmentioning
confidence: 99%
“…Overall, the recent widespread availability of LFP sensing technology embedded in commercial DBS devices offers unprecedented access to objective real-world data and promises a faster path to personalized care for DBS patients. Nonetheless, this large and growing amount of sensing data now being made available by DBS and potentially other neuromodulation devices highlights a critical need for the development of specialized algorithms, tools and infrastructure in order to provide the most potential benefit for patients (Chen et al, 2021).…”
Section: A Role For Local Field Potentials Signals In Supporting the ...mentioning
confidence: 99%